Evaluation of anticancer potential of Bacopa monnieri L. against MCF-7 and MDA-MB 231 cell line - Md. Nasar Mallick; Md. Salman Akhtar; Mohd Zeeshan Najm; E T Tamboli; Sayeed Ahmad; Syed Akhtar Husain (Wolters Kluwer Medknow Publications, 2015)
Background: The ethanolic extract of Bacopa monnieri contains bacoside A and B, brahmin, cucurbitacins, and betulinic acid. Currently, cucurbitacins have also been reported for their strong anti-tumorigenic and anti-proliferative activity by inducing cell cycle arrest at the G2/M phase and formation of multiplied cells. The present study was carried out to evaluate the in vitro cytotoxic activity of ethanolic extract of dichloromethane (DCM) fraction of B. monnieri on two different cell lines. Materials and Methods: The ethanolic extract of B. monnieri was prepared using soxhlet extraction method and different fractions (hexane, DCM, methanol, acetone, and water) of ethanolic extracts were prepared. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay of ethanolic extract and of all fractions was carried out on MCF-7 and MDA-MB 231 cell lines. The presence of cucurbitacins and betulinic acid in these fractions was confirmed by high-performance thin layer chromatography. Results: The IC50 values of ethanolic extract of B. monnieri in MCF-7 and MDA-MB 231 cell lines were 72.0 μg/mL and 75.0 μg/mL, respectively. The DCM fraction of B. monnieri showed maximum cytotoxic activity among all fraction upto 72 h and was found to be 57.0 μg/mL and 42.0 μg/mL, respectively. Conclusion: The results showed good cytotoxic activity in DCM fraction in both the cell lines may be due to the presence of cucurbitacins and betulinic acid in DCM fraction.